Anti-Money Laundering and Combating the Financing of Terrorism : Inclusion in Surveillance and Financial Stability Assessments. (Policy Papers; Policy Paper, 2012)
This note provides guidance on the inclusion of AML/CFT issues in surveillance and financial stability assessments (FSAs). Specifically, it provides a framework for the treatment of cases where money laundering or terrorist financing (ML/TF) and related underlying crimes (i.e., 'predicate crimes' or 'predicate offenses') are so serious as to threaten domestic stability, balance of payments stability, the effective operation of the International Monetary System-IMS- (in the case of Article IV surveillance), or the stability of the domestic financial system (in the case of FSAs).